Analysis of District Reg. Magelang Number 6 of 2011 Concerning Health Service Charges at the Muntilan Regional General Hospital Reg. Magelang - Nur Zanis; Vicki Dwi Purnomo; Benedictus Hestu Cipto Handoyo; Syukron Abdul Kadir (Journal of Legal and Cultural Analytics, 2022)
Regional regulations (perda) are a manifestation of the authority granted to regional governments in the context of implementing regional autonomy and co-administration tasks as well as accommodating special regional conditions and/or further elaboration of higher laws and regulations. What is the process of forming the Regional Regulation of Magelang Regency Number 6 of 2011 concerning Health Service Retribution at the Muntilan General Hospital, Kab. Magelang, whether it represents local wisdom or not. Local wisdom in foreign languages is often conceptualized as local wisdom (local wisdom), local knowledge (local knowledge) or local intelligence (Ideal genious). Local wisdom is the attitude, view, and ability of a community in managing its spiritual and physical environment, which gives the community resilience and power to grow in the area where the community is located. In other words, local wisdom is a creative answer to geographical-geopolitical, historical and situational situations.